2020
DOI: 10.3991/ijet.v15i04.11687
|View full text |Cite
|
Sign up to set email alerts
|

Development and Integration of E-learning Services Using REST APIs

Abstract: E-Learning systems have gained a lot of traction amongst students and academicians due to their flexible nature in terms of location independence, time, effort, cost and other resources. The rapidly changing nature of the education domain makes the design, development, testing, and maintenance of E-Learning systems complex and expensive. In order to adapt to the changing policies of educational institutes as well as improve the performance of students, the paper presents a Service-Oriented Architecture (SOA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Fourth, from an architectural point of view, the application presents as a novelty, on the one hand, being developed as a layer of REST-type web services, which offers the advantage that the modification and addition of new services [33] is very simple, since all services are independent of each other, and the only thing they share is information from the common database that they all use. On the other hand, the mixed system that combines a web application with an Android application is also original [34] for this type of system. This architecture delegates responsibility for maintaining consistency and synchronization of data in the common database used by the two applications.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, from an architectural point of view, the application presents as a novelty, on the one hand, being developed as a layer of REST-type web services, which offers the advantage that the modification and addition of new services [33] is very simple, since all services are independent of each other, and the only thing they share is information from the common database that they all use. On the other hand, the mixed system that combines a web application with an Android application is also original [34] for this type of system. This architecture delegates responsibility for maintaining consistency and synchronization of data in the common database used by the two applications.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, this process became increasingly time-consuming, especially when the number of students in a class is exceptionally large during virtual classes additionally, handling the attendance information of a large gathering can be difficult. One of the disadvantages of the current system is that students can use fake attendance stamps during their virtual classes (Swamy kutti et al, 2000). So, to solve those issues we developed an app with automatic facial attendance system.…”
Section: Facial Recognition Attendancementioning
confidence: 99%
“…This task has been successfully implemented and the e-learning system 2.0, which makes it possible to measure the key student success factor (student involvement), has already been introduced. The solution is implemented with the help of the information dashboard aimed at visualizing student participation in the virtual learning environment [15]. It has been concluded that visualization in education not only raises awareness but also has a versatile function.…”
Section: Introductionmentioning
confidence: 99%